2016
DOI: 10.1089/omi.2016.0123
|View full text |Cite
|
Sign up to set email alerts
|

How Does Chronic Cigarette Smoke Exposure Affect Human Skin? A Global Proteomics Study in Primary Human Keratinocytes

Abstract: Cigarette smoking has been associated with multiple negative effects on human skin. Long-term physiological effects of cigarette smoke are through chronic and not acute exposure. Molecular alterations due to chronic exposure to cigarette smoke remain unclear. Primary human skin keratinocytes chronically exposed to cigarette smoke condensate (CSC) showed a decreased wound-healing capacity with an increased expression of NRF2 and MMP9. Using quantitative proteomics, we identified 4728 proteins, of which 105 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 73 publications
2
22
1
Order By: Relevance
“…Nam treatment significantly inhibited the increase of cytokines and prostaglandins synthesized after stress and significantly restored the reduced levels of Lamin B1 (a biomarker known to be lost during senescence) induced by UVB exposure. Relative to cigarette smoke, it has been reported that exposure to keratinocytes can elicit a strong oxidative stress response based on proteomics [41]. We did not detect as strong of a cytokine induction but did see a significant effect of Nam at inhibiting the induced levels of the prostaglandin PGE2.…”
Section: Discussioncontrasting
confidence: 72%
“…Nam treatment significantly inhibited the increase of cytokines and prostaglandins synthesized after stress and significantly restored the reduced levels of Lamin B1 (a biomarker known to be lost during senescence) induced by UVB exposure. Relative to cigarette smoke, it has been reported that exposure to keratinocytes can elicit a strong oxidative stress response based on proteomics [41]. We did not detect as strong of a cytokine induction but did see a significant effect of Nam at inhibiting the induced levels of the prostaglandin PGE2.…”
Section: Discussioncontrasting
confidence: 72%
“…In addition to oxidative stress, the increase in air pollution over the years has been suspected to also play a role in human skin ageing process [8][9][10][11][12][13][14]. A clinical study performed in a polluted environment revealed significant skin differences in superficial biochemical parameters measured on the face of volunteers such as a decrease in squalene, a lipid specific to human sebum which is highly sensitive to oxidation with regard to its six double bonds [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Nam treatment significantly inhibited the increase of cytokines and prostaglandins synthesized after stress and significantly restored levels of Lamin B1 (a biomarker known to be lost during senescence) that were reduced by UVB exposure. Relative to cigarette smoke, it has been reported that exposure to keratinocytes can elicit a strong oxidative stress response based on proteomics [36]. We measured an elevated response in PGE 2 production and Nam treatment inhibited these induced levels and also partially reversed the most significant gene expression patterns that were related to apoptosis, DNA repair and cell cycle regulation.…”
Section: Discussionmentioning
confidence: 90%